Pengembangan Pariwisata Desa Kuwu Berbasis Potensi Lokal - Suwarti Suwarti; Tri Maryani (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This activity is a community service activity in the context of implementing the Tridarma of Higher Education, for postgraduate lecturers at STIEPARI Semarang. The implementation was in March 2023, the location of the activity was the Kuwu tourism village, Kradenan District, Grobogan Regency, Central Java. The purpose of the activity is to introduce the community to the development of Kuwu Village tourism based on Local Tourism Potential. This activity is not only an effort to improve the ability of tourism village management but also as a means of introducing the basics of tourism village development, because Kuwu village although it has had a decree as a pilot tourism village since 2009, but there are no real activities in the village. The implementation technique is direct socialization, to people who have local potential home industry businesses such as Ayam Pencok, and various flavors of meatballs, and crispy chicken, PAU. The system of delivering socialization material uses direct in the field (visits to residents who have a business and continued with a question and answer discussion.